Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae) - Ota, Renata R.; Carvalho, Fernando R.; Pavanelli, Carla S. (Zootaxa, 2020)
A taxonomic review of the Hyphessobrycon panamensis species-group is presented, with recognition of six valid species. In Central America, H. panamensis was restricted to the drainages of both Atlantic and Pacific coasts of Panama; H. savagei was recorded at the río Pírris and río Térraba, Pacific coast of Costa Rica, and Hyphessobrycon bussingi, new species, described from the río Sixaola basin, Atlantic coast of Costa Rica, and from the río Changuinola, río Guarumo and río San San, Atlantic coast of Panama. At trans-andean South America, H. columbianus was recorded at the río Acandí, Colombia, and its geographical distribution was extended into the coastal drainages in San Blas province, Panama; H. condotensis was recorded at the río Atrato, río Baudó, lower río Magdalena and río San Juan basins, Colombia, while H. sebastiani was considered as its junior synonym. Hyphessobrycon daguae was revalidated, erected to the specific level, considered as senior synonym of H. chocoensis, and recorded from the río Dagua, río Patía and río Telembí basins, in Colombia, the río Mira, at the border between Colombia and Ecuador, and the río Cayapas, río Mataje, and río Santiago, in Ecuador. Color pattern and secondary sexual characters (e.g. number, arrangement and shape of hooks in mature males) suggest that the Hyphessobrycon panamensis species-group is a putatively monophyletic lineage.